Tailings and mine waste '08 : proceedings of the 12th Tailings and Mine Waste Conference, Vail, Colorado, USA, 19-22 October 2008.: proceedings of the 12th Tailings and Mine Waste Conference, Vail, Colorado, USA, 19-22 October 2008. (©2009) - Unknown
No abstract available